Effectiveness of Coagulation Profile as a marker for blood loss in Elective Craniotomy patients - Sajid Rashid, Hasnain Khan, Yasir Iqbal, (Journal of Rawalpindi Medical College, 2021)
Objective: The objective of this study is to determine the role of preoperative coagulation studies in predicting intraoperative blood loss, in patients undergoing elective craniotomy in our tertiary hospital setting. Materials and Methods: This was a Quasi-experimental study conducted at Department of Neurosurgery, Aga Khan University Hospital Karachi for a duration of 6 months. A non-probability consecutive sampling technique was employed. All admitted neurosurgery patients for elective craniotomy were enrolled and followed as part of the study. Laboratory values including baseline workup e.g. Complete Blood count, PT, activated Partial Thromboplastin Time (aPTT), Internationalized Ratio (INR) were taken preoperatively and postoperatively. A predesigned questionnaire for the collection of data was used, which included demographics and clinical information. Approval from the university ethical committee was obtained before starting the study. Data was entered and analysed into SPSS version 21. Effect modifier age, gender, co-morbids, type, and duration of surgery, were controlled through stratification. Post-stratification paired t-test and independent-sample t-test were applied using P ≤ 0.05 as significant. Results: In this study 57 patients who underwent elective craniotomy were included to assess the mean blood loss and to compare mean blood loss in patients with normal and deranged coagulation profiles. The mean age of patients included in the study was 39.36±13.94 years with 43 (75.4%) males and 14 (24.6%) females. The mean preoperative haemoglobin level amongst all patients turned out to be 14.10±3.98 gm/dl. The postoperative haemoglobin level showed a decrease with a mean of 12.68±31.98 gm/dl. Therefore the mean difference calculated between pre and post-operative haemoglobin levels turned out to be 1.42±0.99 gm/dl. Conclusion: It is to be concluded that significant change was found in preoperative and post-operative Haemoglobin levels in patients undergoing elective craniotomy. There was also a highly significant difference in blood loss between patients having a normal versus deranged coagulation profile. However, there is a need to conduct more studies using a large sample size with multiple study sites in Pakistan to validate these results.